The effects of laser acupuncture dosage at PC6 (Neiguan) on brain reactivity: a pilot resting-state fMRI study - Chang, Yi-Chuan; Chen, Chun-Ming; Lay, Ing-Shiow; Lee, Yu-Chen; Tu, Cheng-Hao (Frontiers in Neuroscience, 2023)
Previous studies indicated that laser acupuncture (LA) may effectively treat various medical conditions. However, brain responses associated with LA intervention have not been fully investigated. This study is focused on the effect of LA with different energy density (ED) in brain using resting-state functional magnetic resonance imaging (fMRI). We hypothesized that different ED would elicit various brain responses. We enrolled healthy adults participants and selected bilateral PC6 (Neiguan) as the intervention points. LA was applied, respectively, with ED of 0, 7.96, or 23.87 J/cm2. Two 500-s resting-state fMRI scans were acquired before and after intervention, respectively. The functional connectivity (FC) was calculated between autonomic nerve system-regulation associated brainstem structures and other brain regions. Compared to other dosages, the FC between rostral ventrolateral medulla and orbitofrontal cortex has more enhanced; the FC between caudal ventrolateral medulla, nucleus of the solitary tract/nucleus ambiguus, and dorsal motor nucleus of the vagus and somatosensory area has more weakened when ED was 23.87 J/cm2. Different dosages of LA have demonstrated varied regions of FC changes between regions of interest and other brain areas, which indicated that variations in EDs might influence the clinical efficacy and subsequent impacts through distinct neural pathways within the brain.